PENGUKURAN KEBERGUNAAN SISTEM INFORMASI KEGIATAN GEREJA BERBASIS WEB MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Yoshua, Alexandre; Zaman, Baizul; Surasa, Hendra (JTRISTE, 2025)
This study aims to measure the quality of the Jadwal Ibadah website based on usability, information quality, and interaction quality in relation to user satisfaction. Data was collected through a questionnaire distributed to 30 respondents and analyzed using the System Usability Scale method. The System Usability Scale method is used to produce a user interface design that meets user needs and wants, as well as to determine the usability level of a system. The website testing results yielded a score of 62, which is rated as Good. Therefore, it can be concluded that the design of the Jadwal Ibadah website user interface solves user problems and provides more accurate and precise information.